2018
DOI: 10.3389/fmats.2018.00029
|View full text |Cite
|
Sign up to set email alerts
|

Facile MoS2 Growth on Reduced Graphene-Oxide via Liquid Phase Method

Abstract: Single and few-layers MoS 2 were uniformly grown on the surface of chemically reduced graphene oxide (r-GO), via a facile liquid phase approach. The method is based on a simple functionalization of r-GO with oleyl amine which seems to affect significantly the MoS 2 way of growth. Scanning-transmission-electron microscopy (STEM) analysis revealed the presence of single-layer MoS 2 on the surface of a few-layers r-GO. This result was also confirmed by atomic-force microscopy (AFM) images. X-ray photoemission spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Concerning the review articles encompassed in the Carbon-Based Materials section published in Frontiers in Materials journal, very significant contributions may be found in which the importance of knowing and modulating the properties of carbon materials are detailed. That is the case of the review published by Macovez (2018), who revisited some of the physical properties of organic fullerene cocrystals compared to pristine C 60 , which are endorsed by the incorporation of different types of molecules. Some other review papers emphasise the importance of modulating the surface chemical properties of carbon materials in order to attain promising catalysts for a given application.…”
Section: Characterisation and Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the review articles encompassed in the Carbon-Based Materials section published in Frontiers in Materials journal, very significant contributions may be found in which the importance of knowing and modulating the properties of carbon materials are detailed. That is the case of the review published by Macovez (2018), who revisited some of the physical properties of organic fullerene cocrystals compared to pristine C 60 , which are endorsed by the incorporation of different types of molecules. Some other review papers emphasise the importance of modulating the surface chemical properties of carbon materials in order to attain promising catalysts for a given application.…”
Section: Characterisation and Propertiesmentioning
confidence: 99%
“…The outstanding method is a combination of the Langmuir-Schaefer (LS) deposition technique combined with two self-assembly steps. In another report, Salavagione et al (2018) reported diverse methods to prepare functional fibers and fabrics that contain graphene. Generally, graphene is incorporated into a polymer solution that is later subjected to wet spinning or electrospinning to obtain the composite fibers.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[59] Graphene, on the other hand, has a limited flow and is hydrophobic, which restricts its application in biosensors. [60] The hydrophobicity of graphene oxide (GO) and decreased graphene oxide (rGO) was control by increasing the hydrophilicity of the graphene layer. The removal of the oxygen groups of GO, resulting in exceptional electrical properties and simplicity of surface alteration for biomolecule immobilization.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…As it has a greater particular surface area than CNTs, graphene, a two‐dimensional hexagonal arrangement of carbon atoms [59] . Graphene, on the other hand, has a limited flow and is hydrophobic, which restricts its application in biosensors [60] . The hydrophobicity of graphene oxide (GO) and decreased graphene oxide (rGO) was control by increasing the hydrophilicity of the graphene layer.…”
Section: Emerging Techniquesmentioning
confidence: 99%